2009
DOI: 10.1161/circresaha.109.202440
|View full text |Cite
|
Sign up to set email alerts
|

Evidence From Human Myectomy Samples That MYBPC3 Mutations Cause Hypertrophic Cardiomyopathy Through Haploinsufficiency

Abstract: (Figure 1). 1 MyBP-C is likely to have both structural and regulatory roles within the sarcomere, and recent data have suggested that MyBP-C has a role in relaxation and stretch activation. 2,3 The physiological importance of MyBP-C has been further highlighted with the discovery of mutations in MYBPC3 as the most commonly identified cause of hypertrophic cardiomyopathy (HCM), typically being found in Ϸ20% to 25% of patients screened; more than 150 different mutations have been reported. 4,5 In striking cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
199
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(224 citation statements)
references
References 21 publications
18
199
0
3
Order By: Relevance
“…Finally, haploinsufficiency was also reported in HCM with MYBPC3 missense mutations (23), including the mutation investigated in our study (E258K). Indeed, samples with MYBPC3 mut missense mutations in our study showed a 22 ± 9% reduction in cMyBP-C protein level compared with donors.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…Finally, haploinsufficiency was also reported in HCM with MYBPC3 missense mutations (23), including the mutation investigated in our study (E258K). Indeed, samples with MYBPC3 mut missense mutations in our study showed a 22 ± 9% reduction in cMyBP-C protein level compared with donors.…”
supporting
confidence: 73%
“…Recent evidence supports that the N-terminal extension of cMyBP-C binds the low-Ca 2+ -state (B-state) position of tropomyosin on actin and interferes with tropomyosin-actin interactions, dislocating tropomyosin into the C-state position (i.e., the presence of cMyBP-C sensitizes the thin filament to Ca 2+ ) (20,21). Because it was previously shown that in Ca 2+ -free conditions (B state) ∼5% of the thin filaments (lacking cMyBP-C) have tropomyosin localized in the C-state position (10), more myofilaments may be in the C state in the presence of cMyBP-C. We (22) and others (23) have shown that cMyBP-C mutations, which are a major cause of HCM, have a reduced level of healthy cMyBP-C protein compared with nonfailing hearts (i.e., haploinsufficiency), which may alter tropomyosin position on the thin filament.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…In myectomy specimens from patients with an MYBPC3 truncation mutation, protein content was reduced by 24-33% compared with transplant donor, or non-MYBPC3 myectomy specimens 6,7 .…”
mentioning
confidence: 94%
“…This is mainly because missense mutations in β‐MHC that cause HCM result in incorporation of mutant proteins into the sarcomere, whereas the majority of mutations in cMyBPC that cause HCM often result in the production of truncated cMyBPC peptides, which are not incorporated into the sarcomere as they are likely removed by cellular quality control mechanisms such as non‐sense‐mediated mRNA decay or ubiquitin‐proteasome systems 24. The net result is decreased incorporation of full‐length cMyBPC into the sarcomere leading to haploinsufficiency 7, 8, 25, 26. Functionally, decreased incorporation of cMyBPC in human HCM samples expressing cMyBPC truncation mutations led to accelerated XB kinetics at submaximal Ca 2+ activations, in part, contributing to cardiac hypercontractility and hypertrophy 27.…”
Section: Introductionmentioning
confidence: 99%